Trade, labor share, and productivity in India's industries - Dibyendu Maiti (Asian Development Bank Institute (ADBI), 2019)
This paper explores whether trade can explain a part of the sharp decline in the labor share of Indian formal industries from around 30% in 1980 to less than 10% in 2014. Decline in strikes and lockouts, reduced labor time lost from disputes per factory and increased use of contract workers in all major states in India are signs of reduced bargaining power. In order to estimate the influence of trade, the mark-up and bargaining power affecting the labor share and resultant productivity is derived. A semi-parametric approach is applied on a 3-digit level of industrial data over major states during 1998-2014 to regress Solow residual (the proxy for productivity) on trade share along with its interaction terms capturing market imperfections. The results confirm that trade, by dampening the bargaining power of labor, reduces labor share and hence raises productivity. It is argued that the joint effects of market size and competition arising out of trade cannot dominate the adverse effect of specialization in the presence of unions. The degree of specialization or comparative advantage that appears due to the increased market share of the most productive firms, who require fewer workers, thereby reducing the demand for workers with the trade. The drop in demand weakens bargaining power and shifts away distributive share from workers. But the competitive policy encouraging entry can negate such adverse effects of trade, to a large extent.
Keywords: D24; F16; L11; 330; trade; market imperfections; labor share and productivity growth